Case Report: 21 Cases of Umbilical Hernia Repair Using a Laparoscopic Cephalic Approach Plus a Posterior Sheath and Extraperitoneal Approach - Zhang, Kunjie; Qin, Mingfang; Ding, Guoqian (Frontiers in Surgery, 2021)
Purpose: In this study, a novel surgical technique was developed for umbilical hernias, in which a laparoscopic cephalic approach plus a posterior sheath and an extraperitoneal approach was employed. The aim of this study was to determine the results of this new technique. Methods: From 2019 to 2020, 21 patients (81.8% men) with an umbilical hernia underwent a laparoscopic cephalic approach plus a posterior sheath and extraperitoneal approach, performed by two surgeons specializing in abdominal wall surgery, in two academic hospitals. Intraoperative and postoperative complications, operation time, blood loss, and hernia recurrence were assessed. Results: 21 cases of umbilical hernia were successfully completed. The size of the hernia ring was 1.5–3 cm2, with an average of 2.39±0.47 cm2. The operation time was 120–240 min (average, 177.3±42.15 min), and the blood loss volume was 30–40 ml (average, 33.73±3.55 ml). The mean follow-up period was 6 months, and there were no short-term complications and no cases of recurrence. Conclusion: A laparoscopic cephalic approach plus a posterior sheath and extraperitoneal approach is a safe alternative for the repair of an umbilical hernia. The intraoperative complication rate was low.